Development of Bustarah Media to Introduce Reading and Writing Literacy to Early Children in Historical Tourism Exploration in Palembang - Amalia, Sherly; Farida, Farida; Raharjo, Makmum; Sumarni, Sri (FKIP - Universitas Riau, 2025)
This study aims to develop a historical pocket book (BUSTARAH) as a learning medium to enhance early childhood (AUD) literacy through an educational tourism exploration approach grounded in the local potential of Palembang. The research is motivated by the need for contextual and engaging literacy media that connect children’s learning experiences with real-life environments, particularly through the introduction of historical sites as authentic learning resources. The development process followed the ADDIE model, encompassing needs analysis, design, development, implementation, and evaluation. Validation results indicated a high level of feasibility, with material expert ratings reaching 95%, media experts 100%, language experts 85%, and teacher practicality scores at 97%, demonstrating that BUSTARAH is suitable and easy to use in classroom settings. Its effectiveness was further assessed through learning outcome improvements, reflected in an increase in the average score from 18.5 (pre-test) to 31.2 (post-test), accompanied by an N-Gain score of 0.79 in the moderate category. These findings confirm that BUSTARAH effectively enhances early literacy skills by providing exploratory and meaningful learning experiences aligned with children’s developmental needs, particularly through direct engagement with local cultural and historical heritage.